Modeling Visual Attention of Students Playing an Educational Game for Physics - Vicente, Celesamae T (Archīum Ateneo, 2011)
This study models the visual attention of students as they think of a solution to a problem within an educational game for Physics. Participants were given time to view a hint followed by a static image of the game problem. Upon viewing the problem, students were instructed to think of a solution using the hint while an eye tracker recorded eye movement data. After viewing the problem, participants played the actual game level. The game awarded gold, silver, or no badges to participants depending upon their performance. When analyzing the relationship between the eye movement and performance, the findings were that participants who earned gold, silver, and no badges had different orders of fixating on the regions of interest while thinking of a solution to the problem and participants who had better performance fixated earlier on the regions where the solutions should have been drawn.